Gut microbiota composition in recurrent acute otitis media: a cross-sectional observational study - Florjan, Andrej; Rupnik, Maja; Mahnic, Aleksander (Folia microbiologica, 2024)
Recurrent acute otitis media (rAOM) poses a significant challenge in children aged 1 to 6 years, characterized by frequent and treatment-resistant ear infections. While existing studies predominantly focus on alterations in the nasopharyngeal microbiome associated with rAOM, our research explores the understudied association with the gut microbiome. In this cross-sectional observational prospective study, we enrolled 35 children aged 1 to 6 years during the 2021/2022 cold season. The test group comprised children with rAOM (n = 16), and the control group consisted of generally healthy children (n = 19). Samples (stool and nasopharyngeal swabs) were collected in late spring to ensure an antibiotic-free period. Detailed metadata was gathered through a questionnaire examining factors potentially influencing microbiota. Microbiota composition was assessed through amplicon sequencing of the V3-V4 region of the 16S rRNA gene. Our findings revealed limited alterations in gut microbiota composition among children with rAOM compared to healthy controls. Six bacterial taxa (Veillonella, Lachnospiraceae, Ruminococcaceae, Lachnospiraceae, Bacteroides and Blautia) were differentially represented with weak statistical significance. However, several bacterial taxa displayed correlations with multiple consecutive infections, with Turicibacter showing the most significant association. Additionally, day care centre attendance emerged as a potent gut microbiota modifier, independent of rAOM. Although our study identified limited differences in gut microbiota composition between children with rAOM and healthy controls, the observed correlations between the number of infections and specific bacterial taxa suggest a potential link between rAOM and the gut microbiota, warranting further investigation.
Keywords: recidiva; Recurrent acute otitis media; Gastrointestinal Microbiome; Infant; feces; Humans; kojenec; dítě; Child; Female; RNA ribozomální 16S; Metagenomics; lidé; RNA, Ribosomal, 16S; Otitis Media; Feces; předškolní dítě; Nasopharynx; Gut microbiota; ženské pohlaví; Male; nazofarynx; Cross-Sectional Studies; Recurrence; střevní mikroflóra; Bacteria; Turicibacter; mužské pohlaví; prospektivní studie; otitis media; Child, Preschool; Acute Disease; průřezové studie; akutní nemoc; Prospective Studies